Biopreservative nisin: its application to fishery products - Yusro Nuri Fawzya (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2010)
The need for safe food products amid increasingly perceived widespread use of various foodadditives which are sometimes hazardous to health. Preservative is one of food additives intendedto extend the shelf life of food products. The preservative produced by lactic acid bacteria isbacteriocin. Nisin, one of bacteriocin produced by LAB Lactococcus lactis,is considered safeand allowed its use in many countries, including Indonesia. This preservative is widely used forfood products due to its ability in inhibiting bacteria, especially Gram-positive bacteria such asClostridium botulinum, Staphylococcus aureus, Streptococcus hemolyticus, Listeriamonocytogenes, Bacillus stearothermophilus, and Bacillus subtilis.Nisin works actively at lowpH and can be used singly or in combination with other preservation treatments. Based on itsphysico chemical properties and bioactivity, the use of nisin in fishery products is more suitable infermentation process as well as fish canned in acidic medium such as tomato sauce.